Formulasi dan Analisis Nilai Gizi Bakso Kotak dari Jamur Tiram Putih (Pleurotus Ostreatus): Formulation and Analysis of Nutritional Value of Square Meatballs from White Oyster Mushroom (Pleurotus ostreatus) - Lamadjido, Sri Rahayu; Umrah, Umrah; Jamaluddin, Jamaluddin (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2019)
Meatballs are processed meat products that very popular in Indonesia. Making meatballs is not just using animal material only, but also can be used plant materials such as oyster mushrooms. The meatballs can be made in various forms, such as a round shape or a box shape. This study aims to determine the nutrient content (moisture, ash, fat, protein, and carbohydrates) in several formula meatballs box of oyster mushroom (Pleurotus ostreatus) and find the best formula on the meatballs box oyster mushrooms, the nutrients (fat, protein, and carbohydrates), as well as the ash and moisture content. The study was designed using completely randomized design (CRD), which consists of six treatments and two replications. Parameters measured were as hedonic organoleptic include color, aroma, flavor and texture, using 15 panelists and nutrient analysis includes the levels of fat, protein, carbohydrate, ash content and water content. The results showed that the formulation of meatballs box, panelists preferred the formula II from another formula with a value of 3.06 based on color, aroma, flavor, and texture. The results of nutritional analysis were fat content of 0.77, protein content of 16:28 value, carbohydrate content of 31.4, ash content of 1:46 and water content of 9.44.